“Justice was Refused Me, I Resolved to Free Myself”: John W. Lindsay. Finding Elements of American Freedoms in British Canada, 1805-1876 - Broyld, Dann (Ontario History, 2017)
Though born a free man, John W. Lindsay at the age of seven was abducted by slave catchers and enslaved in Washington D.C. He eventually landed in Western Tennessee where he made a declaration that he intended to emancipate himself no matter the cost. In order to receive the rights, liberties, and immunities granted to natural-born white men in the United States constitution, Lindsay had to flee to the border town of St. Catharines, Ontario. This article will reconstruct the principally unknown life of Lindsay as he negotiated nations, helped to build a Black community in Canada out of American refugees, and resolved to live in citizenship and equality with his contemporaries.